Studies Of Antimicrobial Agent (Aa) Filled With Polypropylene (Pp) For Antimicrobial Application - Faudzi, Ku Nur ‘Izzati Ku Mohamad Faudzi (2013)

(untitled)
Microbial infection is well recognized as a global threat to human health in biomedical field. Infections caused by microbes in hospitals are associated with usage of medical equipment and devices especially catheter. In this study, polymer matrix composite materials was produced by incorporated CuO and TiO2 particles into polypropylene through mixing process in Haake internal mixer at 185°C for 10 minutes followed by compression moulding process. Parameters used included variety composition of PP, CuO, TiO2, Ag, AgNO3 and ZnO and temperature of cooling process at QCW (10°C), QWW (30°C), CP and SC. Characterizations used included optical microscope, SEM, XRD, DSC and antimicrobial testing (embedded method and colony count). There were three stages involved like effect of using different types of AA embedded in PP matrix, effect of mixture of two to three different types of AA and colouring agent embedded in PP matrix and effect of different cooling conditions. At stage 1, CuO/PP and TiO2/PP shows good distributions particles and good antimicrobial testing which were then used in next stage. PP/CuO/TiO2/C had been selected as the best sample because of well distribution AA in PP matrix, low crystallinity and good antimicrobial resistance. Quenching method in warm water made PP/CuO/TiO2/C sample more amorphous and increase antimicrobial efficacy. Conclusively,PP/CuO/TiO2/C has high potential to reduce infection caused by microbes. It also can be used as new replacement to current catheter in biomedical application